Whether Plasma Endocrine And Biochemical Profile Can Predict Early Pregnancy In Mares - Rabari, M.l.; Shah, R.G.; Tank, P.H.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
This work was carried out on 32 mares selected randomly from different areas of Saurastra region of Gujarat state during March-August, 2011. The mares bred naturally were subjected to per rectal examinations between day 20 and 150 post-breeding together with periodic blood sampling and were divided into pregnant (22) and non-pregnant (10) groups. The pregnant mares were further distributed in three stages as per the gestation days, viz., i) Stage-I: 0-35 days of gestation (4), ii) Stage-II: 36-75 days of gestation (7), iii) Stage-III: 76-150 days of gestation (11). The mean plasma progesterone level (ng/ml) of pregnant mares was significantly higher in stage-III (20.34 ± 2.13) followed by stage-I (15.55 ± 3.54) and II (13.51 ± 1.81), whereas in non-pregnant mares significantly lower mean P4 level (0.97 ± 0.15) was observed. The mean plasma estradiol-17β concentration (pg/ml) was significantly higher (P< 0.05) in pregnant mares of stage-III (289.82 ± 73.05) than those in stage-I (28.50 ± 4.52) and II (43.14 ± 11.90), and even in non-pregnant ones (23.80 ± 1.82). The mean plasma total cholesterol level was significantly (P<0.05) higher in non pregnant mares than the pregnant mares of stage-II, I and III. The mean plasma protein levels did not differ significantly between various stages of pregnancy and non-pregnancy. The mean plasma glucose level was significantly higher at stage-III of pregnancy (101.40 ± 5.38 mg/dl) and calcium level was significantly lower in Stage-I (10.65 ± 0.26 mg/dl) as compared to other stages. The mean plasma inorganic phosphorus (mg/dl) value was significantly higher during stage-III of pregnancy (3.97 ± 0.06 mg/dl). The close interrelationships were observed between cholesterol and triglycerides, progesterone, estradiol, and pregnancy days with glucose level. Thus, the detection of higher level of estradiol-17β (>126 pg/ml) and progesterone (> 8.2 ng/ml) during 76- 150 days post-breeding can be used as diagnostic marker for early pregnancy in mares.